Regulatory Challenges Facing Remote Working in Australia - Dayaram, Kantha; Burgess, John (IGI Global, 2021)
This chapter examines the industrial relations and workplace challenges associated with increasing remote work in Australia. First, the chapter reports on responses obtained from 11 in-depth interviews with human resource and industrial relations practitioners to assess the support and barriers for continuing and or increasing the uptake of remote work post COVID-19. It then examines the Australian industrial relations framework to determine its support of extending flexible work arrangements for a wider scope of workers.